Diseño e implementación de un módulo experimental para simular procesos de control industrial, en el laboratorio de la carrera de Ingeniería Eléctrica en Sistemas Eléctricos de Potencia de la Universidad Técnica de Cotopaxi Campus La Matriz en el periodo 2020-2021. - Andy Tanguila, Jorge Joel (2021)
This technological proposal about the "Design and Implementation of an Experimental Module in order to simulate industrial control processes in the laboratories of the Electrical Engineering major at Power Electric Systems, at the “Universidad Técnica de Cotopaxi", based on manual and automatic control of motors, and automatic systems. The main objective was to design and implement an experimental didactic module that allows adequate training and learning of students, through the use of devices such as protection, maneuvering, control and force; carrying out practices and simulations of processes that are similar to those existing professionals filed and in the industrial area. The practices focus on the basic control methods wired up to programmable logic control through a PLC LOGO. It facilitates the performance of motor start-ups, such as direct start-up, rotation reversal, dynamic braking as well as soft start-up, instant start-up, soft braking, instantaneous braking, all this by means of the existing frequency inverter in the module. The purpose of the practices is that students have a progressive learning and with their progress a greater degree of difficulty, directly benefiting the students of the “Universidad Técnica de Cotopaxi”, Faculty of Engineering and Applied Sciences.